Cine MRI assessment of motility in the unprepared small bowel in the fasting and fed state: Beyond the breath‐hold. Issue 1 (19th September 2018) - Khalaf, Asseel; Nowak, Adam; Menys, Alex; Marciani, Luca; Taylor, Stuart A.; Spiller, Robin C.; Gowland, Penny A.; Moran, Gordon W.; Hoad, Caroline L.
Abstract: Background: The symptoms of functional bowel disorders are common in postprandial but investigations are generally undertaken in the fasted state using invasive procedures. MRI provides a noninvasive tool to study the gastrointestinal tract in an unperturbed, fed state. The aim of this study was to develop a technique to assess small bowel motility from cine MRI data in the unprepared bowel in fasting and fed states. Methods: Fifteen healthy volunteers underwent a baseline MRI scan after which they consumed a 400 g soup. Subjects then underwent a postprandial scan followed by further scans at regular intervals. Small bowel motility was assessed using single‐slice bTFE cine MRI. An optimized processing technique was used to generate motility data based on power spectrum analysis of voxel‐signal changes with time. Interobserver variability (n = 15) and intra‐observer (n = 6) variability were assessed. Changes in the motility index were compared between fasted and immediate postprandial state. Key Results: Excellent agreement between observers was seen across the range of motility measurements acquired, with intraclass correlation coefficient (ICC) of 0.979 (P < 0.0001) and Bland‐Altman limits of agreement 95% CI: −28.9 to 45.9 au. Intra‐observer variability was low with ICC of 0.992 and 0.960 (2 observers, P < 0.0001). Changes from the fasted to immediately postprandial state showed an average increase of 122.4% ± 98.7% (n = 15). Conclusions & Inferences: This optimized technique showed excellent inter and intra observer agreement. It was sensitive to changes in motility induced feeding. This technique will be useful to study contractile activity and regional patterns along the gastrointestinal tract under physiological conditions. Abstract : This study presents an optimized analysis technique (AUCpower spectrum) to evaluate small bowel motility in the fasting and postprandial states using Cine MRI datasets. This method showed sensitivity to changes in motility induced by ingestion of a meal when compared to a previously published metric for motility, SDJAC. Cine MRI scanning is available on most clinical scanners; therefore, future studies have real potential to translate and improve our knowledge of the small bowel environment in health and disease.